The Hidden Dangers of Land Disputes: Why Proof of Ownership Matters in Civil Lawsuits - Anand, Ghansham (Journal of Judicial Review, 2024)
One of the legal issues regarding civil lawsuits related to land and building rights is "whether or not the description of evidence of ownership of land and building rights is mandatory in the description of the lawsuit". This still causes dualism because there is a legal vacuum in this regard. The objectives of this article are: 1) Analyze the position of the description of proof of ownership in a lawsuit regarding land and building rights issues; and 2) Analyze the ratio decedendi regarding the parsing of proof of ownership in a lawsuit regarding land and building rights issues. This research is doctrinal research with statute, conceptual, and case approaches. The results of this study are, first, related to the description of evidence of ownership of land rights in the lawsuit as a formal requirement of the lawsuit in the issue of disputes over land and building rights is an obligation then the lawsuit can be qualified as an obscure lawsuit (obscuur libel), and of course the juridical consequence is that the lawsuit cannot be accepted (niet ontvankelijke verklaard). Second, from the consideration of the panel of judges in the Cibinong District Court Decision Number 216/Pdt.G/2023/PN Cbi. and District Court Decision 15/PDT.G/2011/PN. GORONTALO, it can be concluded that according to the Panel of Judges, the description of evidence of ownership of land rights in the lawsuit is a formal requirement that must be fulfilled.